The Professional Work of Hinge Objects: Interprofessional Coordination in Urban Drainage - Marie Leth Meilvang (Professions and Professionalism, 2018)
Recent developments in sustainable urban drainage have turned the area, formerly controlled by engineers, into a professional field encompassing engineers, landscape architects, and urban planners. Through interviews, fieldwork, and docu-ment analysis of three Danish cases of urban rainwater management, the article shows how these three different professions, in drawing upon the specific Danish concept of LAR (Local Diversion of Rainwater), compete with each other but also coordinate their work tasks. The article proposes the concept of hinge object, in-spired by Star and Griesemer’s boundary object and Abbott’s work on hinges, to capture how LAR serves as a coordinating object among professions, but also among professions, the state, and universities.